2020
DOI: 10.1002/er.5855
|View full text |Cite
|
Sign up to set email alerts
|

Construction of hollow structure cobalt iron selenide polyhedrons for efficient hydrogen evolution reaction

Abstract: The development of highly active, robust and cost-effective noble metal-free electrocatalysts for hydrogen evolution reaction (HER) in alkaline solution remains a severe challenge. In this work, a hollow structure CoSe 2-FeSe 2 heterojunction electrocatalyst (denoted by "(Co,Fe)Se 2 ") was designed by a simple anion exchange reaction and selenization. Benefiting from the unique hollow structure, the (Co,Fe)Se 2 catalyst accelerates diffusion of electrolyte, besides, the CoSe 2-FeSe 2 heterojunction could provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Xue et al observed that Co Fe mass ratio in (CoFe)Se 2 has a profound effect on its HER activity. [317] In their work, ZIF-67 was used as a self-sacrificial template as well as the source of Co for preparation of CoFe Prussian blue analogs (PBA), which were then transformed into (CoFe)Se 2 hollow structures by direct selenization (Figure 17k,l). The hollow architecture of as prepared polyhedron possessed a high electrochemically active surface area while the synergism among FeSe 2 and CoSe 2 boosted the intrinsic activity of the catalyst.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xue et al observed that Co Fe mass ratio in (CoFe)Se 2 has a profound effect on its HER activity. [317] In their work, ZIF-67 was used as a self-sacrificial template as well as the source of Co for preparation of CoFe Prussian blue analogs (PBA), which were then transformed into (CoFe)Se 2 hollow structures by direct selenization (Figure 17k,l). The hollow architecture of as prepared polyhedron possessed a high electrochemically active surface area while the synergism among FeSe 2 and CoSe 2 boosted the intrinsic activity of the catalyst.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Reproduced with permission. [ 317 ] Copyright 2020, John Wiley and Sons. n) Schematic of the synthetic procedure used for the preparation of Co‐VS ex , Co‐VSx, and Co‐VOx.…”
Section: Zif‐67 and Its Derivatives As An Electrocatalysts For Water ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Kirkendall effect properly explained the diffusion and exchange reactions between metal cations and sulfide/oxygen anions during the sulfidation/oxidation processes. [68,69] Shen et al synthesized NiCo 2 S 4 hollow nanoparticles with a "ball-in-ball" configuration by using the anion-exchange method. [70] As schematically illustrated in Figure 3C, NiCoglycerate solid nanoparticles were employed as the precursor…”
Section:  Kirkendall Effectmentioning
confidence: 99%
“…Water electrolysis is one of the most promising processes for hydrogen generation and involves the hydrogen evolution reaction (HER). [1][2][3][4][5] However, this process is restricted by the sluggish kinetics of the HER. Therefore, electrocatalysts are typically employed to enhance the HER performance.…”
Section: Introductionmentioning
confidence: 99%